2018
DOI: 10.1111/tpj.14067
|View full text |Cite
|
Sign up to set email alerts
|

TBL10 is required for O‐acetylation of pectic rhamnogalacturonan‐I in Arabidopsis thaliana

Abstract: O-Acetylated pectins are abundant in the primary cell wall of plants and growing evidence suggests they have important roles in plant cell growth and interaction with the environment. Despite their importance, genes required for O-acetylation of pectins are still largely unknown. In this study, we showed that TRICHOME BIREFRINGENCE LIKE 10 (AT3G06080) is involved in O-acetylation of pectins in Arabidopsis (Arabidopsis thaliana). The activity of the TBL10 promoter was strong in tissues where pectins are highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 63 publications
(115 reference statements)
5
26
0
Order By: Relevance
“…This provides important insight into the previously uncharacterized function of PMR5. The activity on OGAs suggests that PMR5 acetylates homogalacturonan domains of pectin, unlike the recently reported TBL10, which is specific for RG‐I domains (Stranne et al ., ). Neither pmr5 nor tbl10 is devoid of acetylation of the respective pectin domains, suggesting that additional members of the large TBL family are involved in pectin acetylation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This provides important insight into the previously uncharacterized function of PMR5. The activity on OGAs suggests that PMR5 acetylates homogalacturonan domains of pectin, unlike the recently reported TBL10, which is specific for RG‐I domains (Stranne et al ., ). Neither pmr5 nor tbl10 is devoid of acetylation of the respective pectin domains, suggesting that additional members of the large TBL family are involved in pectin acetylation.…”
Section: Discussionmentioning
confidence: 97%
“…Characterized proteins from the TBL/DUF231 family include a diversity of cell wall modifiers: AXY4 (acetylation of xyloglucan) (Gille et al ., 2011b; Zhu et al ., ), TBR (trichome birefringence), a gene involved in cellulose biosynthesis (Bischoff et al ., ), ESK1 (eskimo 1) involved in the acetylation of xylan (Xin et al ., ; Yuan et al ., ; Urbanowicz et al ., ), TBL3 and TBL31, which are required for the 3‐ O ‐monoacetylation of xylan (Yuan et al ., ), and TBL10, which O ‐acetylates rhamnogalacturonan I (Stranne et al ., ). From another protein family, RWAs (reduced wall acetylation) are likely to function as transporters for acetyl‐CoA from the cytosol to the Golgi lumen to provide substrate for acetylation (Manabe et al ., ), and AXY9 is suggested to produce an acetylated intermediate for the acetylation of xyloglucan (Schultink et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Modulation of the degree of methylesterification (DM) and acetylation by specific enzymes, pectin methylesterases (PMEs) and pectin acetylesterases (PAEs), has been reported to play a major role in controlling the chemistry of pectins and their rheological properties, with consequent effects on plant development (Hocq et al, 2017a). This can notably be illustrated by a number of results showing that dark-grown hypocotyl elongation (Pelletier et al, 2010), root development (Guenin et al, 2011;S en echal, Graff, et al, 2014), pollen grain germination and pollen tube elongation (Jiang et al, 2005;Tian et al, 2006;Gou et al, 2012;Leroux et al, 2015), flower development (Peaucelle et al, 2008;de Souza et al, 2014), plant-pathogen interaction (Osorio et al, 2007;Hewezi et al, 2008;Raiola et al, 2011) and drought stress (Stranne et al, 2018) are altered in Arabidopsis plants for which the expression of either PME or PAE genes is modified. The above-mentioned results can either be a direct consequence of the decrease in the degree of methylesterification and acetylation of HG or an indirect consequence due to the formation of substrates for HGdegrading enzymes.…”
Section: Introductionmentioning
confidence: 98%
“…In Arabidopsis, members of the DUF231 family have been demonstrated to mediate the acetylation of various cell wall polysaccharides. These include MOATs catalyzing mannan O ‐acetylation (Zhong et al ., ), XOATs mediating the regiospecific O ‐acetylation of xylan (Xiong et al ., ; Yuan et al ., , ,b,c; Urbanowicz et al ., ; Zhong et al ., ), AXY4/XGOAT1 and AXY4L/XGOAT2 catalyzing xyloglucan O ‐acetylation (Gille et al ., ; Zhong et al ., ), and TBL10 essential for O ‐acetylation of pectic rhamnogalacturonan‐I (Stranne et al ., ). Phylogenetic analysis showed that Arabidopsis MOATs, AXY4/XGOAT1 and AXY4L/XGOAT2 fall into group II, which contains almost half of moss and Selaginella DUF231 genes, and that TBL10 belongs to group V, which also includes moss and Selaginella members (Fig.…”
Section: Discussionmentioning
confidence: 99%